Izvedba in rezultati akcijske raziskave procesa zdravstveno vzgojnega svetovanja staršem - Urbančič, Klaudia (Obzornik zdravstvene nege, 2001)
The article presents the second set of the results of action research of the process of halth education counseling to parents of prematurely born infants. The article deals with experiencing of parents following premature birth in the Maternity Hospital in Ljubljana, Unit for Intensive Care and Therapy of the Newborn and presents the performance of the program and its results. Action changes are presented in detail. According to authors estimation, the program was successfully implemented into practice: in the conclusion, advantages of the results for management of nursing care, quality of nursing and the analysis of the program and its advantages for the development of research activities in nursing care are presented.
Keywords: Counseling; Health education; Infant care; Infant, premature; Parents; starši; svetovanje; zdravstvena nega; zdravstvena vzgoja